Microwave signals spectru.m analysis by means of microwave photonics - L. A. Aronov; V. N. Ushakov (Известия высших учебных заведений России: Радиоэлектроника)
Approaches for microwave spectral analysis by means of microwave photonics are reviewed. Schemes, algorithms of functioning and possible device’s parameters are discussed.